2018
DOI: 10.1007/s11011-018-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tramadol administration on hippocampal cell apoptosis, learning and memory in adult rats and neuroprotective effects of crocin

Abstract: Tramadol, a frequently used pain reliever drug, present neurotoxic effects associated to cognitive dysfunction. Moreover, crocin has been reported to have neuroprotective effects. The aim of this study was to assess crocin’s capacity to protect learning, and memory abilities on tramadol-treated rats. A total of 35 rats were divided into five groups: Control, Saline, tramadol (50 mg/kg), tramadol + crocin(30 mg/kg), crocin groups and treated orally for 28 consecutive days. Morris water maze (MWM) and passive av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…In PC12 cells, crocin prevents cell apoptosis via increasing glutathione synthesis (16); meanwhile, in aging Wistar rats, crocin enhances their memory abilities, mainly through its anti-oxidant activities (17). In rats administered tramadol hydrochloride, crocin improves their learning and reduces memory impairment (18). However, no systematic study of the effects of crocin on AD, and its underlying mechanisms, has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In PC12 cells, crocin prevents cell apoptosis via increasing glutathione synthesis (16); meanwhile, in aging Wistar rats, crocin enhances their memory abilities, mainly through its anti-oxidant activities (17). In rats administered tramadol hydrochloride, crocin improves their learning and reduces memory impairment (18). However, no systematic study of the effects of crocin on AD, and its underlying mechanisms, has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Tramadol is one of the opioid drugs that is extensively used as a pain-killer for chronic pain and cancers [10]. However, multiple tissue toxicities were reported for patients consuming tramadol medication several times a day [13][14][15][16][17]. Since tramadol like other opioids induces oxidative stress which alters cell structure causing apoptosis [21][22][23][24][25], the pomegranate was used in the current study as a protective agent based on its antioxidant activity [34,35,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol is used to reduce pain resulted from posttraumatic, obstetric, osteoarthritis, fibromyalgia, renal, biliary colic, and neuropathic pain [12]. However, multiple tissue toxicities were reported when tramadol was administrated [13][14][15][16][17], especially for patients consuming tramadol medication several times daily to relieve chronic pain. We and others have shown that tramadol induces testicular toxicity in adults [5,9,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the findings of similar studies. In a study, [48], discovered that treatment of rats with tramadol resulted in an inability of the rats to remember the location of the hidden platform in probe test of Morris Water Maze (MWM).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of neurotoxicity of tramadol have been proven and continuous administration of tramadol has been shown to result in a weight loss of rats' brain [49]. Findings from some recent studies using rodent models have shown that tramadol administration can impair memory functions by activation of µ-opioid receptors [35,48]. Several studies have also indicated that chronic administration of tramadol can cause histological abnormalities such as increasing apoptosis in rat cerebral cortex which is associated with oxidative stress [50], induce seizures [51], lead to increased oxidative stress in various tissues such as the brain [52] and lead to decrease in the expression of some genes in the hippocampus [53].…”
Section: Discussionmentioning
confidence: 99%